3X Academy of Skatepark / Mohd Khairul Mat Jari ... [et al.] - Mat Jari, Mohd Khairul; Beti, Ronald; Dollen, Mohd Azmi; Sindran, Mohd Hafizul; Muhamma Tahir, Ramli (2011)
There are various concept and definitions for skatepark which are not consistently used. However, the word skatepark is normally preferred as an athletic facility that erected and designed specifically for the three major extreme sports which are skateboard, in-line skate and freestyle or flatland BMX. 3X Academy of Skatepark is the first company in Sabah that provides a service in terms of teaching and indoor skatepark based on the three major extreme sports which are Skateboard, BMX and In-Line and at the same time, try to put our best effort in exposing the youth about the most preferable extreme sports in western country like USA. It is a door step for us as a Malaysian to support the efforts allocated for the achievement of one of the nation's goals in promoting the name of Malaysia. Our private indoor skatepark business is very much influenced from the private skatepark in develop western country like USA. For example, California indoor skate park and Texas public skatepark give us inspiration and imagination on how to start private indoor skatepark in term of design of skatepark, services, funding and group community. Since 1970s, the rate for these extreme sports was increased in USA. But, there are a small number of youth in Sabah today being exposed to that kind of sports. Their interest toward the sports should be supported by the local authority and local community through providing the place for them to improve their talents and enhance the popularity of the sports. From the above facts, we can see that the modernization gap between our country with other western countries such as France, USA and England and one of the factors that widening the gap is sport.